Drying Kinetics in Building Materials and Components The Interface Influence - Delgado, João M. P. Q.; Azevedo, António C.; Guimarães, Ana S. (SpringerBriefs in Applied Sciences and Technology,, 2019)
This work presents an extensive experimental characterisation of two different ceramic brick blocks with different interface, at different heights, during the drying process. First, a laboratory characterization of the building material used (ceramic bricks and different mortars) is presented, showing their hygrothermal, mechanical and thermal properties, namely, bulk porosity and density, water vapour permeability, capillary absorption, retention curve, moisture diffusivity as a function of moisture content and thermal conductivity. Moreover, the moisture transfer in multi-layered systems was analysed in detail taking into account the interface contact between the building elements.